Intelligence Quotient (IQ) Relationship with Energy Intake and Micronutrient Composition among Primary School Children in Baghdad City, Iraq - Ghazi, Hasanain Faisal; Isa, Zaleha Md.; Aljunid, Syed; Shah, Shamsul Azhar; Abdalqader, Mohammed A. (Pakistan Journal of Nutrition, 2013)
Nutrient component of diet is very important, especially for children during the development stages. Diet rich in vitamins and minerals is essential for healthy children. This study was conducted to assess the associations between energy intake, macronutrient composition and child Intelligence Quotient (IQ) score. A cross-sectional study was conducted among children aged 7 to 8 years old from 5 primary schools in Baghdad city. Dietary intake was assessed using 24-hour dietary recall. Body weight status was determined using weight and height. While intelligence quotient was evaluated using Raven Colored Progressive Matrices. A total of 480 children participated in this study. The mean age was 8.00±0.56 years. Mean energy intake among the children was 1, 020 kcal per day. There were excessive intake of vitamin B1, B2 and B3 (0.88, 1.12, 12.27 mg) respectively. Both low and normal IQ groups showed a large difference in vitamin A and iodine intakes. After adjusting for confounders, parental working status, Iodine level and child nutritional status still appeared to be the most important factors influencing child IQ. It is concluded that sufficient nutrient intake is very important during child cognitive development. Child nutritional status and iodine deficiency were the most important factors related to child’s intelligence among the respondents.